COMPLETING THE TRIBUNAL: ICTR’S CONTRIBUTIONS AND DEFICIENCIES - Ebru Coban-Ozturk (European Scientific Journal, ESJ, 2014)
The International Criminal Tribunal for Rwanda (ICTR) is an ad hoc tribunal of great significance in terms of international law. The court has completed nearly its twentieth year, while it has been decided to terminate its mission at the end of 2014 after completing its proceedings, since it is an ad hoc tribunal. Concordantly, the judicial power and the ongoing cases will be assigned to national courts and to the Residual Mechanism for Criminal Tribunals, which has been newly established. The Tribunal has left behind many contributions and addressed by some criticisms while coming to an end. The Tribunal, which has numerous contributions to international law, criminal proceedings, regional peace, perception of justice, rule of law, and universal values, deals also with criticisms on issues such as functioning, powers of prosecution, and its limited coverage in terms of region and time span. The contributions of this Tribunal, which is coming to the end of its mission, to international law and reconciliation shall be presented in this study. Then, an overall evaluation of criticisms addressed to the Tribunal and the legal system related with the atrocities in Rwanda.